Color in Mandailing Language: A Semantic Study of Connotation - Ernita Daulay; Mulyadi (Britain International for Academic Research (BIAR-Publisher), 2022)
Language is the way of humans perceives their environment. This paper aim described the study of color semantics in Mandailing language. This is because color is one of the most important elements in human life to convey a certain impression and is an interesting topic to analyze because the vocabulary of color in each language is unique. On this occasion, the authors used the Natural Semantic Metal Language approach to describe Colors in Mandailing Language by using semantic studies of connotation. The method used in this research is a qualitative descriptive method that produces word descriptions. The data technique uses the technique of recording, observing and because of the methods used to obtain data so that it is done by recording using language, both spoken language (Mandailing community speech) and writing related to naming color names. Basically, Mandailing culture recognizes 12 colors, namely red (rara), brown (coklat), gray (abu-abu), purple (bunga torung), orange (pinang), pink (merah jambu), green (rata), light green (rata bulung pisang), blue (rata ombun), white (bontar), black (lomlom) and yellow (gorsing). The function of color in the Mandailing language is also used as a means of communication and social adaptation. In terms of meaning, the color in the Mandailing language also has connotative meanings such as dysphemism and eupemism. The research was conducted in Matondang Village - Palas, North Sumatra with 100% ethnic population in Mandailing. The results of this study indicate that the naming of colors in the Mandailing community in Matondang Village is caused by experience in seeing an object so that when seeing the same color as the object, the naming of the color name appears with the object's name.